2022
DOI: 10.1002/mde.3643
|View full text |Cite
|
Sign up to set email alerts
|

Is corporate philanthropy a pretext for executives' excess perk consumption? Evidence from China

Abstract: Using a sample of Chinese listed firms from 2007 to 2019, we investigate the impact of corporate philanthropy on excess perks. Companies are likely to make philanthropic donations from the motivations of building political connections, serving the personal interests of self‐serving managers, disguising excess perks and deviating public attention, leading to higher excess perks. Agency theory is probably a view to interpret the positive relationship. From the perspectives of CEO power and board effectiveness, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Scholars have found that firms use corporate philanthropy as a window‐dressing tool to shield themselves from public pressure in the wake of corporate environmental scandals (Du, 2015; Wu et al, 2021). Managers may use corporate philanthropy to extract personal benefits (Su et al, 2022) or alleviate personal guilt (Ji et al, 2021).…”
Section: Related Literaturementioning
confidence: 99%
“…Scholars have found that firms use corporate philanthropy as a window‐dressing tool to shield themselves from public pressure in the wake of corporate environmental scandals (Du, 2015; Wu et al, 2021). Managers may use corporate philanthropy to extract personal benefits (Su et al, 2022) or alleviate personal guilt (Ji et al, 2021).…”
Section: Related Literaturementioning
confidence: 99%